Analysis of Planning Guidelines on the Integration of Muslim Cemetery and Recreational Areas - Ibrahim, Putri Haryati; Afla , Mohamad Reza Mohamed; Afla , Mohamad Reza Mohamed; Sarkawi, Azila Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
–Recent studies suggested cemetery to be a dual function to accommodate the needs of open spaces that are gradually diminishing. In Malaysia, the Planning Guidelines for Muslim and Non-Muslim Cemetery need to be referred in developing a burial site because a cemetery is an important social infrastructure in the same way to a recreational park. The focus of this research is to analyze the identification of cemetery as an alternative space for social activities that are compatible with the sanctity of Muslim cemetery. This study attempts to reveal how Muslim cemeteries that are often considered as a dead space can be integrated as part of the city’s recreational park without marginalizing the spiritual values of the space. The methodology employed comprises of (i) comparative analysis on the contents of the cemetery and recreational planning guidelines, and (ii) site observation of the selected case studies as a mean of data collection. The finding exhibits summative points extracted from both the planning guidelines and the physical elements observed that could transform and revolutionized Muslim cemeteries beyond its norm. This article concludes by providing some recommendations that will help to align the planning and design practice of Muslim cemeteries for future development.